SOCIAL THEOLOGY OF CHINESE MUSLIM: FROM ISLAMIC INCLUSIVISM TOWARDS SOCIAL MOVEMENTS - Achmad Muhibin Zuhri; Winarto Eka Wahyudi (UIN Raden Mas Said Surakarta, 2021)
This study examined the role and actions of the Chinese Muslim community in Surabaya, East Java, Indonesia, embodied through an organization called the Indonesian Chinese Islamic Association and the Haji Muhammad Cheng Hoo Indonesia Foundation. Through these two organizations, Chinese Muslims demonstrated anti-mainstream Islamic expressions. They did not so reveal Islamic style, which entirely dominated in rituals and ceremonials. Still, they articulated Islam through social movements to adapt and gain legitimacy from the local Muslims and attract non-Muslim Chinese sympathies on Islam. Based on a qualitative approach, this study found out that by maintaining cultural identity as Chinese, this community ensured that being a good Muslim was not in binary opposition by being authentic Chinese. The experience of the Chinese Muslim community in Surabaya determined that theology was not only a religious issue but also a social problem. Chinese Muslim social theology in Surabaya is an expression of cosmopolitan Islam and successfully well integrated with an inclusive Chinese identity. Social theology demonstrated two dimensions dialectically-integral, the harmonious fusion of Islamic inclusivism and active participation in overcoming various social problems